Evaluation and treatment of premature ventricular contractions in heart failure with reduced ejection fraction. Issue 1 (19th October 2020) - Mulder, Bart A; Rienstra, Michiel; Blaauw, Yuri
Abstract : Premature ventricular complexes (PVCs) are often observed in patients presenting with heart failure with a reduced ejection fraction (HFrEF). PVCs may in some patients be considered to be the cause of heart failure, while in others it may be the consequence of heart failure. PVCs are important prognostic markers in HFrEF. The uncertainty whether PVCs are the cause or effect in HFrEF impacts clinical decision making. In this review, we discuss the complexity of the cause–effect relationship between PVCs and HFrEF. We demonstrate a workflow with the use of a trial period of amiodarone that may discover whether the reduced LVEF is reversible, the symptoms are due to PVCs and whether biventricular pacing can be increased by the reduction of PVCs. The use of non-invasive and invasive (high-density) mapping techniques may help to improve accuracy and efficacy in the treatment of PVC, which will be demonstrated. With these results in mind, we conclude this review highlighting the future directions for PVC research and treatment.